Earnings persistence determinants in Indonesia’s consumer goods companies - Hanum Paramaratri; Christina Tri Setyorini; Irianing Suparlinah (Jurnal Akuntansi dan Auditing Indonesia, 2023)
This study aims to investigate the effect of various financial factors that affect the consumer product sectors in the Indonesia Stock Exchange earnings persistence. The study employed purposive sampling, the data were collected from the 2011-2020 annual financial statements, and analyzed by utilizing panel data regression. In the consumer cyclical industry, firm size and accrual amount negatively influence earnings persistence. In contrast, the impact of fluctuating cash flow, volatile sales, and debt levels was negligible. In the non-cyclical consumer sector, cash flow volatility positively influenced earnings persistence. However, debt levels and accrual amounts had a negative influence, while sales volatility and firm size had no effect. These findings suggest that the determinants of earnings persistence vary by industry and that different financial factors may affect earnings persistence differently. The results may help Indonesian stakeholders in comprehending the factors that affect the sustainability of revenues in the consumer products industry.